AYAT-AYAT AL-QUR’AN DALAM PEMENTASAN DEBUS - Yudi Setiadi (Ushuluna: Jurnal Ilmu Ushuluddin, 2019)
This study discusses the practice of reciting verses of the Qur'an in staging debus. In Debus, the Qur'an, as one of the must reads, has a function outside its textual meaning. The Qur'an is recited for the practical use of its readers. This paper is qualitative method, ethnographic and functional approaches to uncover the meaning and use of the Qur'an in the performance of debus. This research found several findings. Debus players interpret everything they read before staging debus as 1) a means to ask God for help, 2) glorify God, prophets, and trustees- God's guardian, 3) asks for immunity, 4) asks for protection from danger, and 5) asks for salvation.